IN-HOSPITAL MORTALITY WITH NO-REFLOW DURING PRIMARY PERCUTANEOUS CORONARY INTERVENTION - KHAN , K; AKBAR , F; ULLAH , A (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the in-hospital mortality rate associated with No Reflow During Primary Percutaneous Coronary Intervention. The study was conducted at the Peshawar Institute of Cardiology Hayatabad, Peshawar, between January 2023 and June 2023. A total of 90 patients who underwent primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) were included in the study. The incidence of no-reflow during the surgery was observed, and the death rate at six months was recorded. The mean age of the patients was 52.46±10.09 years. Out of the 90 patients, 19 (21.1%) experienced no reflow. No reflow was significantly associated with age, in-hospital mortality, and 3-point MACE (P = 0.03). The study's findings suggest that no-reflow during primary percutaneous coronary intervention is associated with a significant increase in mortality rates in the hospital setting.